Understanding Professional Dynamics in Elderly Care through an Anthropological Lens (Global Journal of Medical Research, 2024)
The objective of this article is to show how the presence of the professional in the activity he is carrying out is linked to his own anthropological constitution This pragmatic anthropological research deals with what man makes with himself It is compared with knowledge from the sociology of work the activity clinic and ergology to highlight the process of reflective awareness as a means of acquiring self-knowledge in professional action This process is based on an objective determination of action from several realms whose relevance has been verified in the professions of support and care carried out in nursing homes through the exploitation of a case study This research aims to identify ways to promote empowerment at work
Keywords: gerontology; professionalism; plural realms; reflective awareness; power to care